A Case of Phlegmonous Gastritis in a Patient with Psoriatic Arthritis on Infliximab. (15th August 2018) - De Davide, Laurence; Beaudoin, Annie
Abstract : Phlegmonous gastritis is a pyogenic infection affecting the submucosa of the gastric wall. Although rarely diagnosed, it remains a disease with high mortality. We thereby describe the case of a 42-year-old male patient known for psoriatic arthritis on Infliximab who was diagnosed with phlegmonous gastritis secondary to immunosuppressive therapy. The patient had a favourable outcome with a conservative treatment consisting of a 14-day course of broad antibiotherapy.